SYSTEMATIC POSITION OF THE SCIAENID CORVINA CAROUNA CUVIER 1830 - Lalmohan, R S (Indian Journal of Fisheries, 2011)
Cuvier (1830) described Corvina carouna based on the specimens collected by Mr. Dussumier from the Malabar coast. Later, Day (1878) and Weber and de Beaufort (1936) synonymised it with Johinus carutta. Trewavas (1977) has considered it to be the synonym of Corvina belangeri Cuvier 1830, a species which has many common characters of Johnius carouna (Cuvier). But when the type specimen of Corvina carouna Cuvier from Museum Nationale d’ Histoire Naturelle, Paris, was examined, it was found to be a valid species, occurring commonly in the Cochin backwaters and estuaries